IMPLEMENTASI KEBIJAKAN EARMARKING TAX PAJAK BAHAN BAKAR KENDARAAN BERMOTOR DI KOTA BEKASI - Devi Purnama Sari; Taufik Silfian; Septian Khaerul Ghany (Jurnal Pajak Vokasi (JUPASI), 2019)
The phenomenon of this study is about implementation Earmarking Tax of Pajak Bahan Bakar Kendaraan Bermotor – Vehicle Fuel Tax having allocation of fund is 70% for reduce of air pollution and environment damage. The purpose of this study is known and analyze of implementation policy earmarking tax vehicle fuels tax in Bekasi City and also entity of support and entity of inhibition on implementation this policy. Method of this study is using qualitative approach with descriptive specificity. The result of this study is implementation policy earmarking tax upon vehicle fuels tax in Bekasi City of West Java to the objective and target policy is as the allocation of funds to pressure the impact of of tax object with target policy is society by focuses to the negative impact of tax object. The activity of the policy on existing tax is in accordance with SOP, but implementation of the allocation fund is not in accordance with regulatations. The result of the activities of the policy of Earmarking Tax PBBKB not yet maximum utilization of allocation funds of activities budgeted. Enity of support has been the use of administrative systems and IT systems in the implementation of the policy of collecting Vehicle Fuel Tax such as Ring Code. While the entity inhibits the policy or rules and organizational structure. Because the Municipal Government of Bekasi has no special regulations governing the allocation of funds. And SKPD associated with the implementation of earmarking tax is still less active and less understanding of the policy.